Infraestrutura logística e o turismo em alagoas no período 2004-2013 - Silva, Bruno Pimentel da (2014)
The state of Alagoas has a beautiful coastline, as well as cultural and historical points of good representation in the country's history. The evolution of the modern world, with momentum of globalization, decreased geographical distances, especially with advances in transportation and communication systems, expanding the meaning and importance of tourism. He ceased to be synonymous with leisure to take the role of social economic agent, politician and, where in many countries is fundamental for development. Thus, tourism is seen as a major opportunity for economic development. Currently only have tourism potential is not enough, you need to plan, invest, explore, energize the sector, so that it has a tourism product that satisfies the desires of tourists. This study aims to analyze the Alagoas tourism sector from the perspective of logistics, which is understood in this case as the distribution channel and sales of tourism products. In this sense, the goal is to understand the behavior of variables connected to the logistics of tourism in Alagoas, for in comparison with the states of Northeast Brazil and the terms, raising a brief diagnosis of the sector. The study found that there were significant increases across the Northeast, in the period from 2004 to 2013, driven by the phenomenon of social mobility of much of the population to consumption classes B and C. However, it was observed in Alagoas investments directed to already established tourist destinations, particularly in the state capital, driven by demand. The domestic market represents 95% of the flow of tourists in Alagoas and the state lacks a strategic plan that is able to consolidate potential tourism products, which can be integrated to existing, expanding its range of destinations, providing major tourist options, according to the segments of tourism offered.